The The Promises and Challenges of Online Extensive Reading in Second or Foreign Language Learning: A Systematic Review - ATIK UMAMAH; DZULFIKRI; DUROTUN NASIHAH (SEAMEO QITEP in Language, 2025)
This study is devoted to investigating the benefits and challenges of online extensive reading (OER) in foreign or second language learning. We applied the four steps of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), such as identification, screening, eligibility, and inclusion. We reviewed relevant studies published between 2009 and 2025 that we identified through major academic international databases (e.g., WoS, Copernicus, and Google Scholar) and Indonesian database, Sinta (Rank 1-2). After screening, we found 25 eligible articles to be reviewed. This study unveils that, to a large extent, online extensive reading can enhance both readers’ affective and cognitive development as well as the possible challenges of OER. In the affective domain, online extensive reading can foster participants’ reading attitude, self-efficacy, and motivation, all of which are central to language learning. Meanwhile, in the cognitive area, online extensive reading significantly contributes to reading comprehension development and vocabulary mastery. However, some studies report that online extensive reading is unable to improve participants’ affective aspects, including reading attitude, self-efficacy, and motivation, as well as cognitive aspects such as reading comprehension and vocabulary mastery, which is partly because of their inability to make use of online features, online reading fatigue, and poor internet connection. This further calls for improvement in those aspects to achieve better online extensive reading promises in language learning.